Cytokines and Inflammation in Meniere Disease - Frejo, Lidia; Lopez-Escamez, Jose Antonio (Clinical and experimental otorhinolaryngology, 2022)
Meniere disease (MD) is a rare set of conditions associated with the accumulation of endolymph in the cochlear duct and the vestibular labyrinth with a decrease of endocochlear potential. It is considered a chronic inflammatory disorder of the inner ear with a multifactorial origin. The clinical syndrome includes several groups of patients with a core phenotype: sensorineural hearing loss, episodes of vertigo, and tinnitus with a non-predictable course. Genetic factors and the innate immune response seem to play a central role in the pathophysiology of the condition. Autoimmune MD should be diagnosed if a patient fulfills the diagnostic criteria for MD and one of the following autoimmune disorders: autoimmune thyroid disease, psoriasis, autoimmune arthritis, ankylosing spondylitis, or systemic lupus erythematosus. We summarize the evidence to support autoimmune MD as an endophenotype in bilateral MD associated with the allelic variant rs4947296 and nuclear factor-kappa B (NF-κB)-mediated inflammation, the role of cytokines (particularly interleukin-1β and tumor necrosis factor-α) in defining a subset of patients with autoinflammation, and the potential role of cytokines as biomarkers to distinguish between patients with MD and vestibular migraine. Finally, we also introduce a list of potential drugs that could regulate the immune response in MD with potential for repurposing in clinical trials.